Medical futility, treatment withdrawal and the persistent vegetative state. - Mitchell, K R (1993)
Why do we persist in the relentless pursuit of artificial nourishment and other treatments to maintain a permanently unconscious existence? In facing the future, if not the present world-wide reality of a huge number of persistent vegetative state (PVS) patients, will they be treated because of our ethical commitment to their humanity, or because of an ethical paralysis in the face of biotechnical progress? The PVS patient is cut off from the normal patterns of human connection and communication, with a life unlike other forms of human existence. Why the struggle to justify ending a life which, it is said, has suffered an irreversible loss of the content of consciousness? Elsewhere, the authors have addressed the ethical controversies and confusion engendered by ambiguous terminology, misuse of medical facts and the differing interpretations of what constitutes 'effective' treatment: in particular, the issue of whether in fact artificial nutrition and hydration is a medical treatment, or simply part of the obligatory care owed to all patients, permanently unconscious or not. In this paper, we intend to argue that recent analyses of medical futility, its meaning and ethical implications, despite an absence of public consensus, permit some tentative re-evaluation of our ethical obligations to the PVS patient.